The Role of Audit Committees on Corporate Governance Effectiveness of Iraqi Special Banks (Filed Study) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
Consistent with developments emerging environmental and canaccept by Iraq of the opportunities and challenges ahead in many fields,including economic areas, it requires the face of those developments andadaptation by adopting a lot of related concepts, including the concept ofcorporate governance and commitment to its principles, standards andmechanisms, especially those related to the formation of audit committeesand identify the tasks and duties entrusted to its members and terms oftheir independence as well as the rehabilitation of both scientific andpractical manner that is consistent with the interests of shareholders andother stakeholders in the companies, including banks, research sample, theresearch aims to shed light on the concept of corporate governance and theimportance of forming audit Committees and identify deficiencies in theCompanies Law (64)- 2004 and the banking Law (94)- 2004 in the signalclearly to the concept of corporate governance and implementationmechanisms, especially those related to the Audit Committee, as it becameclear through the results of the analysis that many of theworking in theresearch sample banks in favor of activating the legal framework thatregulates the work of banks, which would contribute in enhancing theeffectiveness of governance.